1984
DOI: 10.1007/bf01977496
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and sex-independent disposition of ciprofloxacin

Abstract: Serum concentrations and urinary excretion of ciprofloxacin were studied in female and male volunteers following a single oral administration of 100 mg, 250 mg, 500 mg or 1000 mg. Serum and urine concentrations increased proportionally to the increasing dose administered but independently of sex. Twenty-five percent of the administered dose was excreted in the urine as unmetabolized ciprofloxacin within the first 24 hours after oral administration. Renal clearance averaged 5 ml/min X kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
3

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 8 publications
5
25
3
Order By: Relevance
“…In contrast, the pharmacokinetic parameters for ceftazidime calculated by Harding and Harper (9) were similar to those that we calculated. In this study, ciprofloxacin displayed pharmacokinetic parameter values different from those found in other studies (3,5,10,14,38). The maximum concentration in plasma and the area under the concentration-time curve for ciprofloxacin for our subjects were 45 and 34% lower, respectively, than those reported previously (38).…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…In contrast, the pharmacokinetic parameters for ceftazidime calculated by Harding and Harper (9) were similar to those that we calculated. In this study, ciprofloxacin displayed pharmacokinetic parameter values different from those found in other studies (3,5,10,14,38). The maximum concentration in plasma and the area under the concentration-time curve for ciprofloxacin for our subjects were 45 and 34% lower, respectively, than those reported previously (38).…”
Section: Resultscontrasting
confidence: 95%
“…Blood samples were obtained from the cannula inserted in the contralateral arm at 0, 10,20,30, and 45 min and 1, 1.25, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 6, 8, and 12 h following the start of infusion of cefpirome, ceftazidime, ceftriaxone, and imipenem. For ceftriaxone, additional blood samples were obtained at 14,16,24,36, and 48 h following the start of infusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Upon multiple dosing, ciprofloxacin, enoxacin and other fluoroquinolones have shown an increase in the t 1/2 and increased V d from the first dose (Chang et al, 1988;Nix and Schentag, 1988); however, this phenomenon was not observed for norfloxacin in dogs using a dosage regimen of 5 mg/ kg every 12 h for 14 days (Brown et al, 1990) nor for ciprofloxacin in other studies (Höffler et al, 1984;Drusano et al, 1986) nor in dogs (Abadía et al, 1994b). The area under the concentration time curve normalized to a 1 mg/kg dose decreased as the dose of norfloxacin increased from 5 mg/kg to 20 mg/kg in healthy dogs (Brown et al, 1990).…”
Section: Pharmacokineticsmentioning
confidence: 94%
“…The multiple dose phenomenon described by Nix and Schentag (1988) and the non-linearity of the AUC with increasing doses in dogs observed by Brown et al (1990) may reflect a decreased absorption of fluoroquinolones at higher doses, or may be the result of complicated enterohepatic recycling that may occur after repeated doses. The pharmacokinetics seems to be independent of the gender (Höffler et al, 1984) although individual fluoroquinolones may vary depending on the metabolic pathways and routes of excretion.…”
Section: Pharmacokineticsmentioning
confidence: 99%